NAF-1 Inhibition by Resveratrol Suppresses Cancer Stem Cell-Like Properties and the Invasion of Pancreatic Cancer - Qin, Tao; Cheng, Liang; Xiao, Ying; Qian, Weikun; Li, Jie; Wu, Zheng; Wang, Zheng; Xu, Qinhong; Duan, Wanxing; Wong, Lucas; Wu, Erxi; Ma, Qingyong; et al. (Frontiers in Oncology, 2020)
Resveratrol is a natural polyphenolic compound with multiple biological effects, e.g., proliferation inhibition, anti-oxidation, and neuroprotection. Besides that, studies have shown that resveratrol inhibits tumor growth and migration, as well as epithelial–mesenchymal transition (EMT). However, its molecular mechanisms in tumor progression are not fully understood. Nutrient-deprivation autophagy factor-1 (NAF-1) is mainly found in the endoplasmic reticulum and mitochondrial outer membrane. It is an important genetic locus for regulating oxidative stress and autophagy. The molecular mechanism of NAF-1 in pancreatic cancer is currently unclear. The current study found that NAF-1 is expressed in pancreatic cancer tissue and correlated with the progression of pancreatic cancer. Furthermore, we found that NAF-1 inhibition significantly inhibits the stem cell characteristics and the invasion and migration abilities of pancreatic cancer cells. In a subcutaneous xenograft model of pancreatic cancer in nude mice, resveratrol inhibited the expression of NAF-1, thereby inhibiting tumor growth. Taken together, resveratrol could be an effective anti-tumor drug, and NAF-1 may be a rational therapeutic target.